A within-person test of the metacognitive model: Daily dynamics between metacognitive beliefs, metacognitive strategies, and negative affect - Cano-López, Julia B.; Anyan, Frederick; García-Sancho, Esperanza; Nordahl, Henrik; Salguero-Noguera, José Martín (Elsevier, 2024)
The metacognitive model of psychological disorders highlights that emotional distress is maintained by metacognitive strategies, which are related to underlying metacognitive beliefs. Considerable empirical evidence has supported the role of metacognitions in psychopathology, but few studies have examined the suggested links between metacognitive beliefs, metacognitive strategies, and symptoms within individuals. Within-person effects provide better empirical tests of theory-based hypotheses derived from clinical models as they relate to change at the individual level. Thus, the current study sought to test central predictions from the metacognitive model at the within-person level using Dynamic Structural Equation Modelling (DSEM). A sample of 222 participants gathered at convenience participated in a 26-day long assessment period where they reported daily measures of metacognitive beliefs, metacognitive strategies, and negative affect. Temporal precedence and bidirectional relations between the variables, and the possible day-to-day and within days mediation role of metacognitive strategies between metacognitive beliefs and negative affect, were tested. When controlling for previous days effects, metacognitions and negative affect (but not metacognitive strategies) predicted each other the next day, showing a reciprocal relationship. However, metacognitive strategies were significant mediators between metacognitions and negative affect within days and day-to-day. Implications and future directions based on these findings are discussed.
Keywords: Psicología cognitiva; Personalidad; Emociones; Psicología - Metodología; Metacognitive beliefs; Metacognitive strategies; Cognitive attentional syndrome; Emotional regulation; Negative affect